Nickel-based self-supporting hydrogen evolution electrode and preparation method and application thereof

Through the nickel deposition nickel at the foam nickel, nickel -based supporting nitrogen analysis electrodes are prepared, and the problem of insufficient activity and high cost of hydrogen analysis of hydrogen analysis of hydrogen analysis is solved. Essence

CN119352059AActive Publication Date: 2025-01-24CHANGZHOU UNIV

Patent Information

Application Number
CN202411507889.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-24
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing hydrogen evolution electrodes are insufficient in activity under large current density, have high cost and poor stability, making it difficult to meet the requirements of electrolytic water industry applications.

Method used

The nickel -based self -supporting hydrogen analysis method is adopted, and nickel -sedimentary nickel is used to charge nickel nickel through a specific sedimentary system and electrical deposition method.

Benefits of technology

It achieves excellent hydrogen evolution activity at high current density, low overpotential, and performance comparable to noble metal hydrogen evolution electrodes, meeting the needs of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352059A_ABST
    Figure CN119352059A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electro-catalysis full water splitting, and discloses a nickel-based self-supporting hydrogen evolution electrode and a preparation method and application thereof.The preparation method comprises the steps that nickel chloride hexahydrate and terephthalic acid are dissolved in N, N-dimethylformamide, the concentration of the nickel chloride hexahydrate is controlled to be 0.1-0.15 mol / L, the concentration of the terephthalic acid is controlled to be 0.1-0.15 mol / L, the nickel chloride hexahydrate and the terephthalic acid are stirred to be uniform, ultrasonic treatment is conducted, and an electrolyte is obtained; the pretreated foamed nickel is immersed in the electrolyte to serve as a working electrode, a platinum net serves as a counter electrode, an Ag / AgCl electrode is adopted as a reference electrode, current of-10 mA to-20 mA is applied for deposition for 1.5-2.5 h, and the nickel-based self-supporting hydrogen evolution electrode is obtained after electro-deposition and cleaning and drying are conducted. The nickel-based self-supporting catalytic material prepared by the invention fully exposes active sites, has high catalytic performance, has a good application prospect in the technical field of electro-catalytic materials, and is expected to improve energy and environment problems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalytic water splitting, and specifically relates to a nickel-based self-supporting hydrogen evolution electrode and a preparation method and application thereof. Background Art

[0002] Electrocatalytic water splitting is one of the technologies for the efficient production of "green hydrogen". Hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are the two half reactions of water electrolysis, and they are both crucial to the overall efficiency of water electrolysis. However, the large overpotential and slow kinetics of HER and OER seriously hinder the practical application of water splitting. An ideal hydrogen evolution electrode must meet the following requirements: first, it needs to be highly active and can achieve hydrogen evolution at a high current density under a small overpotential; second, it must have good stability. The catalysts used in the currently developed highly active hydrogen evolution electrodes are mainly composed of precious metals such as platinum, palladium, and iridium. Their high price and poor stability limit their application and popularity in water electrolysis. Self-supporting electrodes are a type of excellent electrode that deposits catalysts directly on a conductive substrate. However, many self-supporting electrodes currently exhibit low hydrogen evolution current densities at low overpotentials (for example, the current density is generally less than 1000mA cm at an overpotential of less than 0.25V). -2 ), the preparation process is relatively complicated and it is difficult to meet the requirements of industrial applications of electrolyzed water. For example, a supported nickel-based composite hydrogen evolution catalyst and its preparation method and application disclosed in a Chinese patent document (application number 202011504106.7) include the following steps: first, pretreating the nickel foam to remove the surface oxide; then, loading the Ni nanoparticles on the pretreated nickel foam by electrochemical deposition; then, treating it by cyclic voltammetry to obtain an activated sample; finally, obtaining a Ni(OH)2 / Ni(0) composite hydrogen evolution catalyst by aging. However, due to the limitations of the specific deposition process, the hydrogen evolution activity of the obtained composite hydrogen evolution catalyst is still limited. For another example, a preparation method for growing nickel-copper alloy nanoparticles on nickel foam disclosed in a Chinese patent document (application number 202311171166.5) comprises the following steps: firstly, the cut nickel foam is pretreated by ultrasound in hydrochloric acid, ethanol, and ultrapure water, the treated nickel foam is vacuum dried, and then transferred to a mixed solution of NiCl2·6H2O and Cu(NO3)2·3H2O for electrodeposition. The electrodeposition is carried out in a standard three-electrode electrochemical system (NF, working electrode; platinum electrode, counter electrode; Ag / AgCl, reference electrode) using a chronopotentiometry for constant current deposition. During the electrodeposition process, the cathode current ranges from 100 to 750 mA cm -2 , anode is 0 mA cm-2 , the cathode deposition time is the same as the anode deposition time, ranging from 600 to 1800s, the upper limit voltage is 0 to 10V, and the lower limit voltage is 0 to -10V. Due to the large deposition current and small active area, it is difficult to achieve a large hydrogen evolution current density at a low overpotential. Therefore, it is particularly urgent to develop a low-cost, high-catalytic performance hydrogen evolution electrode. Summary of the invention

[0003] In order to overcome the problem of insufficient activity of hydrogen evolution electrodes at high current density in the prior art, the present invention electrodeposit nickel on nickel foam based on a specific deposition system and an electrodeposition method, and specifically provides a method for preparing a nickel-based self-supporting hydrogen evolution electrode. The nickel deposition layer obtained by the method has high uniformity and high active sites, and has excellent hydrogen evolution activity at high current density.

[0004] In order to achieve the purpose of the present invention, the technical solution adopted is as follows:

[0005] A method for preparing a nickel-based self-supporting hydrogen evolution electrode comprises the following steps:

[0006] The nickel foam is sequentially immersed in 2-3 mol / L hydrochloric acid, ultrapure water and ethanol solution for ultrasonic treatment for 15-20 minutes to obtain a pretreated nickel foam;

[0007] Dissolving nickel chloride hexahydrate and terephthalic acid in N,N-dimethylformamide, stirring evenly, and ultrasonically treating to obtain an electrolyte, wherein the concentration of nickel chloride hexahydrate in the electrolyte is 0.1-0.15 mol / L, and the concentration of terephthalic acid is 0.1-0.15 mol / L;

[0008] The pretreated nickel foam was immersed in the electrolyte as a working electrode for electrodeposition, the platinum mesh was used as a counter electrode, and the reference electrode was an Ag / AgCl electrode. A constant current of -10 to -20 mA was applied for deposition for 1.5 to 2.5 hours.

[0009] After electrodeposition, the loaded nickel foam is washed with DMF, ultrapure water and ethanol, and then vacuum dried to obtain a nickel-based self-supporting hydrogen evolution electrode.

[0010] The above method of the present invention is based on the design of the electrolyte and combined with the control of the electrodeposition parameters under the three-electrode system to deposit a nickel-based self-supporting electrode on the nickel foam. Not only is the raw material system simple and low in cost, but the synthesis steps are also simple. Most importantly, the design of the self-supporting electrode of the present invention reduces the impedance between the material and the substrate, and its uneven morphology increases the specific surface area of ​​the material, exposing larger active sites. The performance of the prepared hydrogen evolution electrode is comparable to that of precious metal hydrogen evolution electrodes, and it has a lower hydrogen evolution overpotential at a high current density, which can meet the needs of industrial applications.

[0011] As a preferred embodiment of the preparation method of the present invention, the size of the nickel foam is 1.0×0.25 cm 2 ~1.0×1.1cm 2 .

[0012] As a preferred embodiment of the preparation method of the present invention, the concentration of nickel chloride hexahydrate in the electrolyte is 0.1 to 0.12 mol L -1 , the concentration of terephthalic acid is 0.14~0.15mol L -1 More preferably, the concentration of nickel chloride hexahydrate in the electrolyte is 0.1 mol L -1 , the concentration of terephthalic acid is 0.15 mol L -1 .

[0013] As a preferred embodiment of the preparation method of the present invention, the electrolyte is prepared by ultrasonic treatment, wherein the ultrasonic power is 20 to 25 W L -1 , the ultrasonic time is 30 to 60 minutes.

[0014] As a preferred embodiment of the preparation method of the present invention, the electrodeposition time is 1.5 h.

[0015] As a preferred embodiment of the preparation method of the present invention, the current intensity of the electrodeposition is -15 to -20 mA.

[0016] As a preferred embodiment of the preparation method of the present invention, the current intensity of the electrodeposition is -15 mA.

[0017] Another object of the present invention is to overcome the deficiencies in the prior art and provide a nickel-based self-supporting hydrogen evolution electrode prepared by the preparation method.

[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a nickel-based self-supporting hydrogen evolution electrode for use in electrocatalytic water splitting.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The nickel-based self-supporting catalytic material prepared by the present invention not only has high deposition uniformity, but also fully exposes the active sites and has high catalytic performance. It has good application prospects in the field of electrocatalytic material technology and is expected to improve energy and environmental problems.

[0021] (2) The nickel-based self-supporting hydrogen evolution electrode of the present invention has excellent physical and chemical properties and platinum-like catalytic performance, and is one of the ideal candidates to replace the precious metal hydrogen evolution electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 HER activity diagram of the hydrogen evolution electrode in an embodiment of the present invention.

[0023] Figure 2 It is a Tafel curve of the hydrogen evolution electrode in the embodiment of the present invention.

[0024] Figure 3 The NiO of the hydrogen evolution electrode in Example 3 of the present invention x SEM image of the morphology and structure of / NF-15mA.

[0025] Figure 4 The NiO of the hydrogen evolution electrode in Example 2 of the present invention x SEM image of the morphology and structure of / NF-10mA.

[0026] Figure 5 Schematic diagram of an electrodeposition device in an embodiment of the present invention.

[0027] Figure 6 These are photos of the electrodeposition of the hydrogen evolution electrodes of Example 6, Example 7 and Example 3.

[0028] Figure 7 HER activity diagram of the hydrogen evolution electrode of Example 6, Example 7 and Example 3.

[0029] Figure 8 HER activity diagram of the hydrogen evolution electrode of Example 8, Example 9 and Example 3. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] Although transition metals are widely used in HER reactions, traditional catalysts are usually in powder form. When constructing electrodes, they need to be prepared in advance as a suspension and coated on a current collector such as glassy carbon. In addition, in order to improve stability, expensive binders (such as Nafion or PTFE reagents) are also required. However, the addition of polymer binders in experimental operations will seriously reduce the electrochemical performance of the catalyst because it increases the series resistance of the electrocatalyst, inhibits the effective diffusion of electrons and covers part of the active sites of the catalyst. These shortcomings greatly limit the further research and application of catalysts. Therefore, optimizing and improving traditional catalysts has become a key issue in the field of HER. The strategy of nickel-based self-supporting electrocatalysts has successfully solved the above problems. This is because nickel-based self-supporting electrocatalysts have the following advantages: (1) Self-supporting systems often have higher conductivity. For example, the electrocatalyst synthesized using nickel foam (NF) as the supporting substrate has a 3D integrated framework with high conductivity, which provides a large number of electron transfer channels and is conducive to the rapid occurrence of chemical reactions; (2) Compared with traditional catalysts, self-supporting catalysts grown directly on the substrate in situ are not easy to agglomerate, and the specific surface area is greatly increased, which can expose more active sites, and a large number of active sites are crucial for catalytic reactions; (3) In a multi-metal catalyst system, the synergistic effect between different phases will also greatly promote HER activity; (4) Self-supporting nanostructured electrocatalysts can be directly used as conductive cathodes for HER testing.

[0034] In the traditional coating method, due to the addition of Nafion reagent, the hydrogen evolution activity of the catalyst will be greatly reduced, and the adhesion of the catalyst is poor. The large amount of H2 bubbles generated during the HER process will cause the electrocatalyst coated on the surface of the glassy carbon electrode to fall off, thus affecting subsequent tests.

[0035] The specific preparation method of the hydrogen evolution electrode of the present invention includes the following:

[0036] First, prepare the pretreated nickel foam: immerse the nickel foam in 2-3 mol L -1 Ultrasonication in hydrochloric acid, ultrapure water and ethanol solution for 15 to 20 minutes to obtain pretreated nickel foam; the size of the nickel foam is: 1.0×0.25cm 2 ~1.0×1.1cm 2 ; (Nickel foam source: Suzhou Shengernuo Technology Co., Ltd.)

[0037] Secondly, prepare the electrolyte: dissolve nickel chloride hexahydrate (NiCl2·6H2O) and terephthalic acid (PTA) in N,N-dimethylformamide (DMF) to calculate the concentration of nickel chloride hexahydrate in the electrolyte system to be 0.1 mol / L and the concentration of terephthalic acid to be 0.15 mol L -1(Experimental verification shows that the concentration of nickel chloride hexahydrate in the electrolyte system is 0.1-0.12 mol L -1 , the concentration of terephthalic acid is 0.14~0.15mol L -1 In the three-electrode system of Example 3, the performance of the hydrogen evolution electrode obtained is more than 98% of that of Example 3) The dissolution method can be a commonly used method in the art. The electrolyte dissolution in the following examples adopts: the material system is stirred for 30 minutes, and finally placed in an ultrasonic tank for 120 minutes to ensure sufficient dissolution.

[0038] Then, a nickel-based self-supporting hydrogen evolution electrode material with an ampere-level current density is prepared: the pretreated nickel foam is immersed in an electrolyte as a working electrode, a platinum mesh is selected as a counter electrode, and an Ag / AgCl electrode is used as a reference electrode. A three-electrode system chronopotentiometry (CP) is used to apply different currents for deposition for 1.5 hours (experimental verification shows that the deposition time is within the range of 1.5 to 2.5 hours, and the deposition effect is relatively good. However, if it exceeds this range, the deposition effect will deteriorate. For example, if the deposition time is too long (more than 2.5 hours) and the deposition amount is too much, the active material is easy to fall off; if the deposition time is too short, uneven deposition is likely to occur). After electrodeposition, the loaded nickel foam is repeatedly washed with DMF, ultrapure water and ethanol, and the hydrogen evolution electrode is obtained after vacuum drying (time 4-6 hours, temperature 50-60°C); (the platinum mesh is from Shanghai Leton Industrial Co., Ltd., and the electrodeposition voltage is 1 to 8V, which is direct current)

[0039] Finally, the prepared hydrogen evolution electrode was electrochemically tested using a three-electrode electrolyzer reaction device to test its water-to-hydrogen performance.

[0040] Electrochemical water splitting performance evaluation:

[0041] Tested by Donghua electrochemical workstation;

[0042] In the three-electrode system, the working electrode is loaded with nickel foam, the reference electrode is Ag / AgCl electrode, and the counter electrode is platinum mesh. (See the electrodeposition process and workstation diagram for details) Figure 5 )

[0043] Among them, the three-electrode system studies the two half reactions of water electrolysis, including the reduction reaction at the cathode to produce hydrogen and the oxidation reaction at the anode to produce oxygen.

[0044] The device was tested at room temperature and pressure with 1M KOH as the electrolyte, and the HER performance was tested in a suitable potential range (-1 to -3 V) by the linear sweep method (LSV).

[0045] Then the CV curves were tested continuously at different scan rates (-2 to -3 V);

[0046] Finally, the impedance of the hydrogen evolution electrode was tested.

[0047] Current density based on electrode macro area 500 / 1000mA cm -2 As an indicator for evaluating the catalytic activity of the hydrogen evolution electrode.

[0048] Example 1

[0049] Preparation and testing of hydrogen evolution electrode S1:

[0050] The pretreated nickel foam was immersed in the electrolyte as the working electrode, the counter electrode was a platinum mesh, the reference electrode was an Ag / AgCl electrode, and a three-electrode system chronopotentiometry (CP) was used to apply a current of -7.5 mA (corresponding to a deposition voltage of -1.74 V to -2.48 V) for 1.5 h. After electrodeposition, the loaded nickel foam was repeatedly washed with DMF, ultrapure water and ethanol, and then vacuum dried (time 4-6 h, temperature 50-60 ° C) to obtain the hydrogen evolution electrode S1, referred to as NiO x / NF-7.5.

[0051] The above NiO x / NF-7.5 was tested for electrochemical moisture decomposition and hydrogen. It was found that NiO x / NF-7.5 has certain catalytic properties.

[0052] For HER, the NiO x / NF-7.5 driven at 500 / 1000 mA cm in 1 M KOH electrolyte -2 The overpotentials of the current densities are 242 / 301 mV respectively.

[0053] Embodiment 2:

[0054] Preparation and testing of S2 hydrogen evolution electrode:

[0055] The pretreated nickel foam was immersed in the electrolyte as the working electrode, the counter electrode was a platinum mesh, the reference electrode was an Ag / AgCl electrode, and a three-electrode system chronopotentiometry (CP) was used to apply a -10 mA current (corresponding to a deposition voltage of -2.66 V to -2.05 V) for 1.5 h. After electrodeposition, the loaded nickel foam was repeatedly washed with DMF, ultrapure water and ethanol, and then vacuum dried (time 4-6 h, temperature 50-60 ° C) to obtain the hydrogen evolution electrode S2, referred to as NiO x / NF-10.

[0056] After the above hydrogen evolution electrode was subjected to electrochemical water decomposition hydrogen test, it was found that NiO x / NF-10 has certain catalytic performance. For HER, NiO x / NF-10 driven at 500 / 1000 mA cm in 1 M KOH electrolyte -2 The overpotentials of the current densities are 193 / 256 mV respectively.

[0057] from Figure 4 It can be seen that NiO x / NF-10 has a loose leaf-like morphology. Figure 3 In comparison, its morphology is loose, which is not conducive to sufficient infiltration of the electrolyte and exposure of active sites.

[0058] Embodiment 3:

[0059] Preparation and testing of S3 hydrogen evolution electrode

[0060] The pretreated nickel foam was immersed in the electrolyte as the working electrode, the counter electrode was a platinum mesh, and the reference electrode was an Ag / AgCl electrode. The three-electrode system chronopotentiometry (CP) was used to apply a current of -15 mA (corresponding to a deposition voltage of -2.53 to -3.48 V) for 1.5 h. After electrodeposition, the loaded nickel foam was repeatedly washed with DMF, ultrapure water and ethanol, and vacuum dried (time 4-6 h, temperature 50-60 ° C) to obtain S3, referred to as NiO x / NF-15.

[0061] Hydrogen Evolution Electrode NiO x / NF-15 morphology SEM image see Figure 3 As can be seen from the figure, NiO x The surface of the / NF-15 composite material is rough and uneven, indicating that the growing active substance roughens the smooth surface of the nickel foam, increasing the specific surface area of ​​the hydrogen evolution electrode, thereby increasing the contact area between the electrolyte and the hydrogen evolution electrode, exposing more catalytic active sites, and achieving the purpose of improving the catalytic activity of the hydrogen evolution electrode.

[0062] After the above hydrogen evolution electrode was subjected to electrochemical water decomposition hydrogen test, it was found that NiO x / NF-15 has certain catalytic performance. For HER, NiO x / NF-15 driven at 500 / 1000 mA cm in 1 M KOH electrolyte -2 The overpotentials of the current densities are 149 / 173 mV, respectively.

[0063] Embodiment 4:

[0064] Preparation and testing of S4 hydrogen evolution electrode

[0065] The pretreated nickel foam was immersed in the electrolyte as the working electrode, the counter electrode was a platinum mesh, the reference electrode was an Ag / AgCl electrode, and a three-electrode system chronopotentiometry (CP) was used to apply a current of -20 mA (corresponding to a deposition voltage of -4.57 to -3.45 V) for 1.5 h. After electrodeposition, the loaded nickel foam was repeatedly washed with DMF, ultrapure water and ethanol, and vacuum dried (time 4-6 h, temperature 50-60 ° C) to obtain S4, referred to as NiO x / NF-20.

[0066] After the above hydrogen evolution electrode is subjected to electrochemical water decomposition hydrogen test, it is known that NiO x / NF-20 has certain catalytic performance. For HER, NiO x / NF-20 driven at 500 / 1000 mA cm in 1 M KOH electrolyte -2 The overpotentials of the current densities are 179 / 216 mV, respectively.

[0067] Embodiment 5:

[0068] Preparation and testing of S5 hydrogen evolution electrode

[0069] The pretreated nickel foam was immersed in the electrolyte as the working electrode, the counter electrode was a platinum mesh, the reference electrode was an Ag / AgCl electrode, and a three-electrode system chronopotentiometry (CP) was used to apply a current of -25 mA (corresponding to a deposition voltage of -4.91 to -3.9 V) for 1.5 h. After electrodeposition, the loaded nickel foam was repeatedly washed with DMF, ultrapure water and ethanol, and vacuum dried (time 4-6 h, temperature 50-60 ° C) to obtain S5, referred to as NiO x / NF-25.

[0070] After the above hydrogen evolution electrode is subjected to electrochemical water decomposition hydrogen test, it is known that NiO x / NF-25 has certain catalytic performance. For HER, NiO x / NF-25 driven at 500 / 1000 mA cm in 1 M KOH electrolyte -2 The overpotentials of the current densities are 206 / 282 mV, respectively.

[0071] The HER activity diagram of the hydrogen evolution electrode is shown in Figure 1 As can be seen from the figure, according to η 500 -HER, the catalytic performance of these hydrogen evolution electrodes is in the following order: NiO x / NF-15>NiO x / NF-20>NiO x / NF-10>NiO x / NF-25>NiO x / NF-7.5; press η 1000 -HER, the order of catalytic performance is: NiO x / NF-15>NiO x / NF-20>NiO x / NF-10>NiO x / NF-25>NiO x / NF-7.5;

[0072] Tafel curve of hydrogen evolution electrode (Tafel slope value is obtained by linear fitting using the Tafel equation using the overpotential and corresponding current density data obtained from the LSV curve: η = a + b × logj, where η is the overpotential, a is a constant, b is the Tafel slope, and j is the current density.) See Figure 2 As can be seen from the figure, the Tafel slopes of these hydrogen evolution electrodes are as follows: Ni-MOF-7.5 is 103 mV dec -1 , Ni-MOF-10 is 109.4 mV dec -1 , Ni-MOF-15 is 77.1mV dec -1 , Ni-MOF-20 is 124.4 mV dec -1 , Ni-MOF-25 is 139.8 mV dec -1 Among them, Ni-MOF-15 has the smallest Tafel slope, indicating that it has the highest activity.

[0073] Example 6

[0074] Nickel chloride hexahydrate (NiCl2·6H2O) and terephthalic acid (PTA) were fully dissolved in N,N-dimethylformamide (DMF) as the electrolyte (the concentration of nickel chloride hexahydrate in the electrolyte system was calculated to be 0.1 mol L -1 , terephthalic acid concentration 0.1 mol L -1 ), the pretreated nickel foam was immersed in the electrolyte as a working electrode, a platinum mesh was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. A three-electrode system chronopotentiometry (CP) was used to apply a -15 mA current for deposition for 1.5 h. After electrodeposition, the loaded nickel foam was repeatedly washed with DMF, ultrapure water and ethanol, and after vacuum drying (time 4-6 h, temperature 50-60°C), it was tested and the effect was not good.

[0075] Example 7

[0076] Nickel chloride hexahydrate (NiCl2·6H2O) and terephthalic acid (PTA) were fully dissolved in N,N-dimethylformamide (DMF) as the electrolyte (the concentration of nickel chloride hexahydrate in the electrolyte system was calculated to be 0.2 mol L-1 , terephthalic acid concentration 0.1 mol L -1 ), the pretreated nickel foam was immersed in the electrolyte as a working electrode, a platinum mesh was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. A three-electrode system chronopotentiometry (CP) was used to apply a -15 mA current for deposition for 1.5 h. After electrodeposition, the loaded nickel foam was repeatedly washed with DMF, ultrapure water and ethanol, and after vacuum drying (time 4-6 h, temperature 50-60°C), it was tested and the effect was not good.

[0077] The deposition uniformity of Examples 6 and 7 is compared with that of Example 3. Figure 6 It can be clearly seen from the figure that the deposition uniformity of Examples 6 and 7 is slightly reduced.

[0078] See Example 6 and 7 for activity diagrams. Figure 7 As can be seen from the figure, according to η 500 -HER, the catalytic performance of these hydrogen evolution electrodes is in the following order: Example 3> Example 6> Example 7. 1000 -HER, the order of catalytic performance is: Example 3> Example 6> Example 7.

[0079] Example 8

[0080] Nickel chloride hexahydrate (NiCl2·6H2O) and terephthalic acid (PTA) were fully dissolved in N,N-dimethylformamide (DMF) as the electrolyte (the concentration of nickel chloride hexahydrate in the electrolyte system was calculated to be 0.15 mol L -1 , terephthalic acid concentration 0.2 mol L -1 ), the pretreated nickel foam was immersed in the electrolyte as a working electrode, a platinum mesh was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. A three-electrode system chronopotentiometry (CP) was used to apply a -15 mA current for deposition for 1.5 h. After electrodeposition, the loaded nickel foam was repeatedly washed with DMF, ultrapure water and ethanol, and after vacuum drying (time 4-6 h, temperature 50-60°C), it was tested and the effect was not good.

[0081] Example 9

[0082] Nickel chloride hexahydrate (NiCl2·6H2O) and terephthalic acid (PTA) were fully dissolved in N,N-dimethylformamide (DMF) as the electrolyte (the concentration of nickel chloride hexahydrate in the electrolyte system was calculated to be 0.15 mol L -1 , terephthalic acid concentration 0.15 mol L -1), the pretreated nickel foam was immersed in the electrolyte as a working electrode, a platinum mesh was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. A three-electrode system chronopotentiometry (CP) was used to apply a -15 mA current for deposition for 1.5 h. After electrodeposition, the loaded nickel foam was repeatedly washed with DMF, ultrapure water and ethanol, and after vacuum drying (time 4-6 h, temperature 50-60°C), it was tested and the effect was not good.

[0083] See Example 8 and 9 for activity diagrams. Figure 8 As can be seen from the figure, according to η 500 -HER, the catalytic performance of these hydrogen evolution electrodes is in the following order: Example 3> Example 9> Example 8. 1000 -HER, the order of catalytic performance is: Example 3> Example 9> Example 8.

[0084] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a nickel-based self-supporting hydrogen evolution electrode, characterized in that: The following steps are included: The nickel foam is sequentially immersed in 2-3 mol / L hydrochloric acid, ultrapure water and ethanol solution for ultrasonic treatment for 15-20 minutes to obtain a pretreated nickel foam; Dissolving nickel chloride hexahydrate and terephthalic acid in N,N-dimethylformamide, stirring evenly, and ultrasonically treating to obtain an electrolyte; the concentration of nickel chloride hexahydrate in the electrolyte is 0.1-0.15 mol / L, and the concentration of terephthalic acid is 0.1-0.15 mol / L; The pretreated nickel foam was immersed in electrolyte as the working electrode for electrodeposition, platinum mesh was used as the counter electrode, and Ag / AgCl electrode was used as the reference electrode. A current of -10 to -20 mA was applied for deposition for 1.5 to 2.5 h. After the electrodeposition, it was washed with DMF, ultrapure water and ethanol in turn, and a nickel-based self-supporting hydrogen evolution electrode was obtained after vacuum drying.

2. The method for preparing a nickel-based self-supporting hydrogen evolution electrode according to claim 1, characterized in that: The concentration of nickel chloride hexahydrate in the electrolyte is 0.1-0.12 mol / L, and the concentration of terephthalic acid is 0.14-0.15 mol / L.

3. The method for preparing a nickel-based self-supporting hydrogen evolution electrode according to claim 1, characterized in that: The concentration of nickel chloride hexahydrate in the electrolyte is 0.1 mol / L, and the concentration of terephthalic acid is 0.15 mol / L.

4. The method for preparing a nickel-based self-supporting hydrogen evolution electrode according to claim 1, characterized in that: The electrolyte is prepared by ultrasonic treatment, wherein the ultrasonic power is 20-25 W / L and the ultrasonic time is 30-60 min.

5. The method for preparing a nickel-based self-supporting hydrogen evolution electrode according to claim 1, characterized in that: The current deposition time is 1.5 h.

6. The method for preparing a nickel-based self-supporting hydrogen evolution electrode according to claim 1, characterized in that: The current intensity of the electrodeposition is -15 to -20 mA.

7. The method for preparing a nickel-based self-supporting hydrogen evolution electrode according to claim 1, characterized in that: The current intensity of the electrodeposition was -15 mA.

8. A nickel-based self-supporting hydrogen evolution electrode prepared by the method for preparing a nickel-based self-supporting hydrogen evolution electrode according to any one of claims 1 to 7.

9. Use of the nickel-based self-supporting hydrogen evolution electrode according to claim 8 in electrocatalytic water decomposition.

10. Use of the nickel-based self-supporting hydrogen evolution electrode in electrocatalytic water decomposition as claimed in claim 9, characterized in that: Including controlling the current density of electrocatalytic water splitting in an alkaline environment to 500-1000 mA cm -2 .

Citation Information

Patent Citations

  • A supported nickel-based composite hydrogen evolution catalyst, its preparation method and application

    CN112647092B

  • Preparation method for growing nickel-copper alloy nanoparticles on foamed nickel

    CN116970977A

  • Preparation method and application of nickel self-supporting electrode loaded with ferric hydroxide and manganese carbonate

    CN112342563A

  • Nickel-based oxygen evolution electrode and preparation method and application thereof

    CN114959768A

  • Preparation method of hollow-structure NiCoFe LDH / NF electrocatalyst derived from bimetal organic framework

    CN116770349A

Cited By

  • Ruthenium-nickel-based difunctional self-supporting electrode and preparation method and application thereof

    CN119710760A

  • A ruthenium-nickel based bifunctional self-supporting electrode, its preparation method and application

    CN119710760B